Ceramic coating formation on high Si containing Al alloy by PEO process. (2nd June 2016) - Wang, P.; Li, J.P.; Guo, Y.C.; Yang, Z.; Wang, J.L.
Abstract : Composited ceramic coating was successfully deposited on a cast piston Al–Si system alloy ZAl12Si3Cu2NiMg using plasma electrolytic oxidation (PEO) process, and the coating mechanism that focused on the initial stages was studied systematically. The morphology, composition and microstructure of the PEO coating were analysed in detail by combination of scanning electron microscopy with energy dispersive X-ray system and X-ray diffraction. The results show that the PEO process involved three stages. The anodic oxide films were simultaneously formed on α-Al phase and eutectic Si in the initial first stage of PEO treatment, but no plasma discharge occurred on primary bulk Si phase. Both primary and eutectic Si phases prevented aluminium oxidisation and had great effects on the morphology and composition of coatings at the first stage. When voltage exceeded 300 V, plasma discharge appeared and concentrated on the localised zone of interface between α-Al and Si phase, and Al–Si–O compound formed. The silicon was oxidised into SiO2 and mixed with Al2 O3, which was formed when melted at high temperature. The roughness of coating that formed on bulk particle of silicon containing, silicon dioxide, was greater than that of other coatings that formed on other phases. When the PEO process time was long enough to get stage III, a coating with smooth surface morphology and uniform element distribution was obtained, but the microstructure of inner layer was loose due to the bulk Si existing.